2001
DOI: 10.1086/322016
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of a β‐Glucan Receptor in the Nonopsonic Entry of NontypeableHaemophilus influenzaeinto Human Monocytic and Epithelial Cells

Abstract: Previous reports showed that nontypeable Haemophilus influenzae (NTHi) reside in macrophage-like cells in human adenoid tissue. This study investigated the ability of nonopsonized NTHi and encapsulated H. influenzae type b (Hib) to enter human monocytic and epithelial cells. The number of intracellular bacteria was determined by a viability assay and flow cytometry. To characterize the mechanisms responsible for the internalization of NTHi, different inhibitors of surface molecules, receptor turnover, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 38 publications
7
56
0
Order By: Relevance
“…It has also been reported that bGR are involved in the recognition of nontypeable Haemophilus influenzae in a variety of human cells, including monocytes and eosinophils [46,47]. The presence of Dectin-1 on both these cell types was suggestive that this receptor may be involved in the recognition of these organisms.…”
Section: Function Of the Bgr On Primary Human Macrophagesmentioning
confidence: 88%
“…It has also been reported that bGR are involved in the recognition of nontypeable Haemophilus influenzae in a variety of human cells, including monocytes and eosinophils [46,47]. The presence of Dectin-1 on both these cell types was suggestive that this receptor may be involved in the recognition of these organisms.…”
Section: Function Of the Bgr On Primary Human Macrophagesmentioning
confidence: 88%
“…The goat anti-human vitronectin and fluorescein isothiocyanate (FITC)-conjugated donkey anti-goat pAbs were from Serotec (Oxford, United Kingdom). An antiserum obtained from a rabbit immunized with the clinical isolate NTHi 772 for 3 times at 2-week intervals was also included, as a control (1).…”
Section: Methodsmentioning
confidence: 99%
“…19,22 Recent studies have also shown a role for dectin-1 in the phagocytosis of Haemophilus influenzae by eosinophils. 23 However, the importance of dectin-1 as a PRR and its role in promoting a proinflammatory response to a mycobacterial infection or to bacterial infections in general remains undefined.…”
Section: Introductionmentioning
confidence: 99%
“…19,22 Recent studies have also shown a role for dectin-1 in the phagocytosis of Haemophilus influenzae by eosinophils. 23 However, the importance of dectin-1 as a PRR and its role in promoting a proinflammatory response to a mycobacterial infection or to bacterial infections in general remains undefined.In the present study we assessed the role of various macrophage PRRs in MAPK activation and cytokine production upon mycobacterial infection. We found TLR2 and dectin-1 to work in concert to promote macrophage activation upon mycobacterial infection.…”
mentioning
confidence: 99%